Implementasi Multisensor Dengan Aplikasi Kalla Smart Living Pada Pengembangan Bisnis Properti Hunian Cerdas Berbasis IoT - Syarif Dinan Yahya; Muhammad Syafaat; Fizar Syafaat (Program Studi Teknik Komputer, 2023)
In the ever-growing digital era, smart residential properties based on the Internet of Things (IoT) have become a major highlight in the development of the property industry. Kalla Smart Living Application Development is one of the leading solutions to increase efficiency, security and comfort in the context of smart housing. The research methodology used includes a comprehensive series of stages. First, research begins with designing this application which will be implemented within the existing Kalla Smart Living framework. This involves identifying user needs, selecting appropriate features, as well as planning an intuitive user interface. The testing process is a key step in this research. Functional testing ensures that the application meets specifications and functions properly. The test and analysis results are used to evaluate the impact of developing the Kalla Smart Living application on residents' comfort in using this application. So the final results of this research provide valuable insight into the contribution of this application in supporting smart residential property businesses. The resulting recommendations can be used by property developers and other stakeholders to continue implementing and maintaining this application. From the blackbox testing results, it was found that the gas sensor, fire sensor and air quality sensor can be connected well with the Kalla Smart Living application.